A Pragmatic Analysis Of Command Utterances In The Subtitle Of Action Movies - Widyaningsih, Ayu Fitriana, Agus Wijayanto, Ph.D, Drs. Sigit Haryanto, M. Hum (2013)
This research studied about command utterances in the subtitle of action movies. The aimed of this research were to identify the pramalinguistic forms and to describe the politeness strategies of command utterances used in the subtitle of action movies, especially Hurt Locker movie and The Eagle movie. The writer employed the descriptive qualitative as type of the research. The data source of this research was the action movies, especially Hurt Locker movie and The Eagle movie. The methods of collecting data were documentation method and the steps included watched the action movies, found command utterances, took notes, retyped, and coded the data. The techniques of analyzing data were classified the data in its linguistic form by employing the sentence theory, classified the politeness strategies of command utterances used in the subtitle of action movies by using the theory of politeness, and concluded the discussion to formulate suggestions of another research of command utterances. This result of the analysis showed the variation of the forms and the politeness strategies of command utterances used in the subtitle of action movies. The variation of the forms was presented in the form of sentence types. The writer found 75 data included 4 positive declarative sentences; 61 positive imperative sentences involved 30 data of a positive imperative sentence consisted of a command and 31 data of a positive imperative sentence consisted of two or more commands; 2 negative imperative sentences; 2 interrogative sentences; and 6 combinations of them. Related to the politeness strategy, they were 68 bald on record strategies; 6 positive politeness; and 1 negative politeness.